2021
DOI: 10.3389/fpsyg.2021.723027
|View full text |Cite
|
Sign up to set email alerts
|

What Matters and What Matters Most for Survival After age 80? A Multidisciplinary Exploration Based on Twin Data

Abstract: Given research and public interest for conditions related to an extended lifespan, we addressed the questions of what matters and what matters most for subsequent survival past age 80. The data was drawn from the population-based and multidisciplinary Swedish OCTO Twin Study, in which a sample (N = 699) consisting of identical and same-sex fraternal twin pairs, followed from age 80 until death, provided detailed data on health, physical functioning, life style, personality, and sociodemographic conditions. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Among middle-aged individuals, none of these indicators was significantly related to mortality risk. However, other studies have found that life satisfaction is meaningfully related to mortality (Parker et al, 1992), also in the oldest-old individuals (Johansson and Thorvaldsson, 2021). In a large US panel study (Willroth et al, 2020), a joint model including several hedonic wellbeing indicators in parallel as mortality predictors was employed.…”
Section: Wellbeing and Mortality: The Evidence So Farmentioning
confidence: 99%
“…Among middle-aged individuals, none of these indicators was significantly related to mortality risk. However, other studies have found that life satisfaction is meaningfully related to mortality (Parker et al, 1992), also in the oldest-old individuals (Johansson and Thorvaldsson, 2021). In a large US panel study (Willroth et al, 2020), a joint model including several hedonic wellbeing indicators in parallel as mortality predictors was employed.…”
Section: Wellbeing and Mortality: The Evidence So Farmentioning
confidence: 99%
“…Twin studies consistently show heritability of lifespan of 20%–30% that may be even lower at later ages. The Swedish OCTO Twin Study had 12% heritability of age at death after 80 years ( Johansson and Thorvaldsson, 2021 ). Decades of effort to identify longevity individual genes has identified few candidates, such as the alleles of ApoE and FOXO3A that are shared across human populations.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are important because self-rated health is a good indicator of overall health status accounting for biological, social, mental, and functional aspects perceived by individuals [8,9], and is a strong and independent predictor of premature mortality [10]. Likewise, poor self-rated memory can be a precursor of dementia and cognitive impairment in older adults [11,12], and has also been linked to increased mortality risk [13].…”
Section: Introductionmentioning
confidence: 99%